Population of dengue transmission areas and demographic and socioeconomic factors. Perú, 2010-2023. - Arrasco, Juan (2024)
Introduction: Dengue, a disease widely distributed in Peru, has increased incidence in recent years. Objective: Identify the population that resides in transmission scenarios, analyze the evolution of dengue and its association with demographic and socioeconomic factors. Materials and methods: Descriptive, cross-sectional, ecological study, using data from secondary sources of cases and demographic and socioeconomic information, publicly accessible; units of analysis at the district and national level, period 2010-2023. Incidence, fatality and mortality rates are estimated, and the association between cases and demographic and socioeconomic variables is analyzed. Results: At the national level, in the period 2010-2023, 606,266 cases were reported from 602 districts (408 with continuous transmission and 194 with sporadic cases), 75% of the national population resides in these scenarios. Incidence, mortality and fatality rates increased significantly in the last two decades, a period in which new DENV2 genotypes were introduced. The populations most at risk are: women, adolescents and young people, residents of jungle districts, areas between 500 and 1000 meters above sea level, of districts with the highest HDI (quintile IV 7.05 times the risk compared to quintile I) and with higher NBI (quintile II 4.5 times the risk compared to quintile I). Conclusions: Dengue morbidity and mortality in Peru has progressively increased, intensifying between the years 2010 - 2023, 3 out of 4 Peruvians live in transmission scenarios, there is an association between dengue incidence and the demographic and socioeconomic factors analyzed, which must be considered to prevention and control.